1988
DOI: 10.1161/01.hyp.11.6.523
|View full text |Cite
|
Sign up to set email alerts
|

Renal nerves and the development of Dahl salt-sensitive hypertension.

Abstract: SUMMARY Several experimental forms of hypertension require intact renal innervation for the development or maintenance (or both) of the elevated arterial pressure. We determined the relationships between urinary sodium and water excretion and arterial pressure in Dahl salt-sensitive rats (DS) with innervated (n = 6) and denervated (n = 7) kidneys after switching from a low to a high sodium diet. Arterial pressure significantly increased in both groups within 48 hours after they began to eat an 8% sodium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
0
19
2
Order By: Relevance
“…It has been demonstrated that renal denervation prevents or attenuates some forms of genetic and experimental hypertension in animals such as spontaneously hypertensive rats, 22,23 New Zealand genetically hypertensive rats, 24 2-kidney models of Goldblatt hypertensive rats, 25 lowsodium, 1-kidney hypertensive rats, 26 angiotensin-induced hypertensive rats, 27 and obesity-induced hypertensive dogs, 28 although negative results were reported in Dahl salt-sensitive rats 31 and Lyon hypertensive rats 32 and conflicting results were also obtained in hypertensive models induced by aortic coarctation, 33,34 NO synthase inhibition, 35,36 and deoxycorticosterone acetate salt treatment 37,38 and in the 1-kidney model of Goldblatt hypertensive rats. 39,40 In the present study, bilateral RD depleted the renal tissue NE content by 94% (measured at the end of the experiments, ie, 2 to 4 weeks after RD), suggesting that the denervation procedure was effective and that significant reinnervation had not yet occurred.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that renal denervation prevents or attenuates some forms of genetic and experimental hypertension in animals such as spontaneously hypertensive rats, 22,23 New Zealand genetically hypertensive rats, 24 2-kidney models of Goldblatt hypertensive rats, 25 lowsodium, 1-kidney hypertensive rats, 26 angiotensin-induced hypertensive rats, 27 and obesity-induced hypertensive dogs, 28 although negative results were reported in Dahl salt-sensitive rats 31 and Lyon hypertensive rats 32 and conflicting results were also obtained in hypertensive models induced by aortic coarctation, 33,34 NO synthase inhibition, 35,36 and deoxycorticosterone acetate salt treatment 37,38 and in the 1-kidney model of Goldblatt hypertensive rats. 39,40 In the present study, bilateral RD depleted the renal tissue NE content by 94% (measured at the end of the experiments, ie, 2 to 4 weeks after RD), suggesting that the denervation procedure was effective and that significant reinnervation had not yet occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that DS rats have abnormalities in the sympathetic nervous system (SNS) [88,89] and endothelial function [90,91] , which causes significant vascular resistance. In addition, there is evidence that supports the hypothesis that abnormal modulation of SNS is involved in www.nature.com/aps Sun Y et al Acta Pharmacologica Sinica npg salt-inducd hypertension.…”
Section: The Molecular Variations In Enac and The Risk For Developingmentioning
confidence: 99%
“…22 Yet, it was found that renal denervation of Dahl S rats did not slow the onset or the degree of hypertension in Dahl S rats. 23 Alternatively, the greater increase of CSF Na concentrations in Dahl S rats could lead to the reported greater elevations of plasma arginine vasopressin (AVP) in Dahl S rats compared with Dahl R rats. 22 We have shown that small physiological elevations of plasma AVP can significantly reduce MBF and blunt the acute pressurenatriuresis relationship, 24 so it is possible that AVP could account for reduced medullary perfusion in Dahl S rats with high salt intake.…”
Section: Mbf Responses To High Salt Intake In Dahl S Ratsmentioning
confidence: 99%